Double metal synergistic synthetic urea: an electrocatalytic study. (28th February 2022) - Zhang, Zhijia; Guo, Ling; Du, Jinping; Hou, Yingjun
Abstract : Urea was synthesized from CO2 and N2 electrocatalyzed by doping V and M on an –N–C substrate. Abstract : Due to the synergistic effects of different metal sites, the double atom or multiple atomic catalysts are very promising for use in electrocatalysis. This paper focuses on the synthesis of urea [CO(NH2 )2 ] under the synergistic effects of bimetallics. The heteronuclear diatomic molecular catalysts were designed and screened, and the details and energy information of the elementary reactions were provided from the atomic level using theoretical simulation, which provided a new understanding for the study of the reaction mechanism. It was found that the NbVN6 C catalyst was the best catalyst for the electrosynthesis of CO(NH2 )2 (0.37 eV < 0.44 eV < 0.67 eV < 0.74 eV < 0.84 eV for NbVN6 C, TaVN6 C, WVN6 C, MoVN6 C, ReVN6 C, respectively), and the optimal path was * → *N2 → *NN → *NNH → *NNH2 → *HNNH2 → *H2 NNH2 → *H2 NNH2 –CO2 → *H2 NNH2 –COOH → *H2 NCONH2 . At the same time, compared with the homonuclear diatomic catalyst V2 N6 C, the heteronuclear diatomic molecular catalyst NbVN6 C had a smaller limiting potential (−0.37 V and −0.59 V), which demonstrated the usefulness of this study.